India : Report on Observance of Standards and Codes-FATF Recommendations for Anti-Money Laundering and Combating the Financing of Terrorism. (IMF Staff Country Reports; Country Report, 2011)
India faces a range of money laundering and terrorist financing risks. India continues to be a target for terrorist groups and has been the victim of numerous attacks. Based on a threat assessment, it was found that India's major sources for terrorist financing (FT) were funds/resources from organizations outside India, counterfeiting of currency, and criminal activities. Key recommendations made to India included the need to address the technical shortcomings in the criminalization of both money laundering and terrorist financing and domestic framework of confiscation and provisional measures.